1988
DOI: 10.2135/cropsci1988.0011183x002800060028x
|View full text |Cite
|
Sign up to set email alerts
|

Seed and Soil Treatments to Improve Emergence of Muskmelon from Cold or Crusted Soils

Abstract: Cold soil temperatures, seedling diseases, and soil crusting may limit stand establishment of early-season muskmelons (Cucumis melo L.). We tested the ability of seed and soil treatments to overcome these factors and improve seedling emergence. The seed treatments were seed priming (6 d at 25 °C in aerated 0.3 M KNO3 solution followed by drying) to improve the rate of germination at low temperatures, and metalaxyl [N-(2,6-dimethylphenyl)-N-(methoxyacetyi) alanine methyl ester] fungicide (Apron 25W) to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
5

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
1
8
0
5
Order By: Relevance
“…Some reports recommend this procedure (Bradford et al, 1988;Nascimento, 2003), whereas others indicate deleterious effects (Akers & Holley, 1986;Nascimento, 2003). No differences in the lettuce germination were observed after seed priming in aerated or non-aerated solutions (Cantliffe, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports recommend this procedure (Bradford et al, 1988;Nascimento, 2003), whereas others indicate deleterious effects (Akers & Holley, 1986;Nascimento, 2003). No differences in the lettuce germination were observed after seed priming in aerated or non-aerated solutions (Cantliffe, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has become a common seed treatment that can increase rate, percentage and uniformity of germination or seedling emergence, mainly under unfavorable environmental conditions. Several studies reported the benefits of muskmelon (Cucumis melo L.) seed priming on germination at low temperatures (Nerson & Govers, 1986;Bradford et al, 1988;Dhillon, 1995;Nascimento & West, 2000). Commercial utilization and availability of primed seeds to farmers is still small.…”
Section: Introductionmentioning
confidence: 99%
“…A 17°C, foi observada uma germinação maior e mais rápida nas sementes osmoticamente condicionadas (Tabela 1). Estes dados corroboram com aqueles observados por diferentes autores, em que os efeitos benéficos do condicionamento osmótico na germinação de sementes de melão ocorreram principalmente em condições de baixas temperaturas (Bradford, 1985;Nerson & Govers, 1986;Bradford et al, 1988;Passam et al, 1989;Welbaum & Bradford, 1991;Dhillon, 1995;Olouch & Welbaum, 1996ae Yeoung et al, 1996. Entretanto, Welbaum & Bradford (1991) observaram uma melhor resposta à germinação em baixas temperaturas somente quando se utilizou sementes imaturas de melão durante o condicionamento osmótico; sementes totalmente maduras não se beneficiaram do condicionamento.…”
Section: Resultsunclassified
“…Os efeitos benéficos do condicionamento osmótico na germinação de sementes de melão têm sido previamente reportados (Bradford, 1985;Nerson & Govers, 1986;Bradford et al, 1988;Passam et al, 1989;Welbaum & Bradford, 1991;Dhillon, 1995;Olouch & Welbaum, 1996a;Yeoung et al, 1996e Nascimento & West, 1998, 1999e 2000. Sementes osmoticamente condicionadas geralmente germinam mais rápido do que aquelas não condicionadas.…”
Section: Introductionunclassified
See 1 more Smart Citation